Warsaw Housing Cooperative. City in Action. - Matysek-Imielińska, Magdalena (Springer, 2020)
The book discusses the unknown and remote urban experiment of modernist social practices and dreams of a better tomorrow. It describes the history of the Warsaw Housing Cooperative not as a historical relic or a single case study, but instead analyses this working-class social housing estate – in itself an extremely interesting emancipatory project – from the perspective of contemporary urban studies. It focuses on issues related to the power of architecture, architects and the estate residents themselves: the city's performative actions, problems related to the polycentric character of the city authorities, the opportunities of building urban institutions, and social identities and urban common goods. Inspired by the history of the Warsaw Housing Cooperative, the book investigates how the estate residents, assisted by social reformers (today called urban activists), organised the urban space of performative democracy, and how they developed anti-capitalist, urban-survival strategies and created new lifestyles. It also analyses how passive tenants turned into active citizens claiming their right to the city. The inspiring book is intended for researchers in the field of performative studies, urban sociologists, critical urban studies researchers, animators of social life and urban activists.
Keywords: Wohnungsbaugenossenschaft; Wohnungsbaugesellschaft; Architekturgeschichte; Baugeschichte; Wohnforschung; Stadtforschung; Stadtsoziologie; Neues Bauen; Gemeinschaftswohnen; Architektur(sozialistisch); Sozialreform; Stadtpolitik; Stadtgeschichte